ระบบวิธีคำนวณพื้นที่-เวลา-ความยาวรอยเลื่อนตามแนวเขตรอยเลื่อนสะกาย ตอนกลางประเทศพม่า - เปรมวดี ไตรตั้งวงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
In this study, the prospective areas of the upcoming large earthquake were evaluated along the Sagaing Fault Zone (SF), Central of Myanmar. In order to find out the precursory seismic quiescence of earthquake, a statistical method, called the Region-Time-Length (RTL) algorithm were, therefore, utilized in this analysis. The main dataset are the completeness earthquake catalogue occupied by 3 data source, i.e., i) Incorporated Research Institutions for Seismology (IRIS), ii) The Global Centroid Moment Tensor (CMT) and iii) Thai Meteorological Department (TMD). After improving the earthquake catalogue, i.e., homogenizing the earthquake magnitude, earthquake declustering of foreshock and aftershock, including eliminating the man-made seismicity, 3,781 events with MW>3.5 reported during 1977-2014 were defined as the completeness data meaningful for any seismicity investigation. Thereafter, 8 available events of the MW>3.5 earthquakes were considered for the retrospective test. According to iterative test, it is reveal that r0 = 75 km and t0 = 1.5 years are suitable characteristic parameter for the SFZ. As a result according to the suitable characteristic parameters mentioned above and the present-day seismicity data, it is revealed that there are 2 prospective areas might be generated by the upcoming large earthquakes, i.e., Myitkyina in the north and Naypyidaw in the central parts of SFZ.